2004
DOI: 10.1002/sres.556
|View full text |Cite
|
Sign up to set email alerts
|

Systems thinking and knowledge management: positional assertions and preliminary observations

Abstract: In recent years, there has been significant interest in [knowledge management]. However, the plethora of both conceptual and practitioner literature has provided little consistency regarding key definitions or methodologies that can act to guide practice. This can result in practitioners selecting particular ideas, constructs or language that has weak conceptual grounding and result in ephemeral and [ad hoc] practices. This paper analyses the use of systems thinking for [knowledge management] practices because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…For example, many organizations have adopted military evaluation practices aimed at routinely using after-action review sessions to gain insights from particular experiences in an institutionalized way (Morrison & Meliza, 1999). The use of this system of inquiry enables teams to better understand changes that are needed in future initiatives (Kawalek, 2004). Recent experimental research has found that the performance of individuals who participated in after-event reviews improved significantly compared to those who did not participate in such reviews (Ellis, Ganzach, Castle, & Sekely, 2010).…”
Section: Learning From Failures and Work Unit Performancementioning
confidence: 99%
“…For example, many organizations have adopted military evaluation practices aimed at routinely using after-action review sessions to gain insights from particular experiences in an institutionalized way (Morrison & Meliza, 1999). The use of this system of inquiry enables teams to better understand changes that are needed in future initiatives (Kawalek, 2004). Recent experimental research has found that the performance of individuals who participated in after-event reviews improved significantly compared to those who did not participate in such reviews (Ellis, Ganzach, Castle, & Sekely, 2010).…”
Section: Learning From Failures and Work Unit Performancementioning
confidence: 99%
“…In this way, it may also improve understanding and the ability of knowledge management initiatives to respond to the needs of the organization (Rubenstein‐Montano et al, 2001 ). The systems thinking framework for knowledge management is perceived as important and useful for practitioners, creating solid, and comprehensive foundations (Fei, Meng, & Yoshiteru, 2002 ; Kawalek, 2004 ).…”
Section: Systems Thinkingmentioning
confidence: 99%
“…To address this challenge, it has been argued that a paradigm shift is required, one that considers the development and operation of an IS as a continuous knowledge-based activity (Yu, 2009) utilizing conceptual modeling (G. Guizzardi, Wagner, Falbo, Guizzardi, & Almeida, 2013) as a way to bring together an understanding of complex enterprise phenomena and an attempt to design IS solutions that support agility and dynamic change. This paradigm shift is based on three principles: (a) Systems thinking that considers independent components that form a unified whole (Kawalek, 2004;Wilby, Macaulay, & Theodoulidis, 2011); (b) Abstract thinking implying that one moves away from the physical manifestation of processes (Hans-Georg Fill, 2014); and (c) Operational thinking that considers the dynamics of a business process and in particular its behavior over time (Sterman, 2000). In terms of processes involved there are essentially two activities: (a) model building and critiquing and (b) simulation and group deliberation.…”
Section: Introductionmentioning
confidence: 99%